The effect of turnover on work satisfaction and mental health : support for a situational perspective - Wright, Thomas A. [Verfasser]; Bonett, Douglas G. [Verfasser] (My University, 1992)
"This study finds support for the situational approach to affect determination in a prospective, two-year longitudinal field study. Specifically, turnover was shown to predict changes in subsequent job measures of work satisfaction and mental health. Employees who changed jobs and occupations showed greater increases in both work satisfaction and mental health than employees who only changed jobs or employees who remained in their initial positions. Further research directions are introduced." (author's abstract) ((en)) Auf der Grundlage einer zweijährigen Feldstudie wird der Zusammenhang von Arbeitsplatz- bzw. Berufswechsel und Arbeitszufriedenheit sowie Gesundheit untersucht. Die grösste Zufriedenheit und beste Gesundheit hatten Arbeitnehmer, die sowohl den Arbeitsplatz als auch den Beruf gewechselt hatten. (IAB)
Der Effekt des Arbeitsplatzwechsels auf Arbeitszufriedenheit und mentale Gesundheit
Keywords: G 2.3.1 Arbeitsteilung & -organisation; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 2.4.4 Biografiegestaltung; G 2.3.4 Qualifikationswandel; Arbeitsplatzwechsel; Arbeitszufriedenheit; Gesundheit; Innerbetriebliche Mobilität; Zwischenbetriebliche Mobilität; Berufswechsel; Quantitative Angaben